Subjective Measure of Cognitive Load Depends on Participants’ Content Knowledge Level - Zu, Tianlong; Munsell, Jeremy; Rebello, N. Sanjay (Frontiers in Education, 2021)
Cognitive load theory (CLT) posits the classic view that cognitive load (CL) has three-components: intrinsic, extraneous and germane. Prior research has shown that subjective ratings are valid measures of different CL subtypes. To a lesser degree, how the validity of these subjective ratings depends on learner characteristics has not been studied. In this research, we explored the extent to which the validity of a specific set of subjective measures depends upon learners’ prior knowledge. Specifically, we developed an eight-item survey to measure the three aforementioned subtypes of CL perceived by participants in a testing environment. In the first experiment (N = 45) participants categorized the eight items into different groups based on similarity of themes. Most of the participants sorted the items consistent with a threefold construct of the CLT. Interviews with a subgroup (N = 13) of participants provided verbal evidence corroborating their understanding of the items that was consistent with the classic view of the CLT. In the second experiment (N = 139) participants completed the survey twice after taking a conceptual test in a pre/post setting. A principal component analysis (PCA) revealed a two-component structure for the survey when the content knowledge level of the participants was initially lower, but a three-component structure when the content knowledge of the participants was improved to a higher level. The results seem to suggest that low prior knowledge participants failed to differentiate the items targeting the intrinsic load from those measuring the extraneous load. In the third experiment (N = 40) participants completed the CL survey after taking a test consisting of problems imposing different levels of intrinsic and extraneous load. The results reveals that how participants rated on the CL survey was consistent with how each CL subtype was manipulated. Thus, the CL survey developed is decently effective measuring different types of CL. We suggest instructors to use this instrument after participants have established certain level of relevant knowledge.